Strategi Pemberdayaan Ekonomi Pondok Berbasis Filantrofi Perspektif Ekonomi Syariah (Studi Pondok Pesantren Fajar Hidayah Padang Japang, Lima Puluh Kota) - Rosdiyati, Vivi; Rusyaida, Rusyaida (LPPM Institut Pendidikan Nusantara Global, 2025)
The Fajar Hidayah Islamic Boarding School is an Islamic educational institution that produces kiai, da'i, ustadz, scholars, religious scholars and other scientists who have broad insight both in religious education and in the general field. One of the functions of Islamic boarding schools is: 1) center of excellence (giving birth to thinkers based on religion), 2) human resource (a center that produces human resources in the field of education, 3) agent of development (as a service and empowerment institution towards society). Research Method uses qualitative methods. The research was conducted at the Fajar Hidayah Islamic Boarding School in Padang, Japan, sourced from collecting primary data from newspapers, interviews, social media (Instagram, Facebook) along with field research. Data analysis in this research uses SWOT analysis, namely the EFE, IFE matrix and score weight table. The results of this research show that economic empowerment based on philanthropy from a sharia economic perspective on the FH Farm business is influenced by the strength of the business in exploiting business opportunities where product quality is good, livestock prices are affordable and, people's purchasing power is high because livestock care and cleanliness is maintained and the area is large. The location of the livestock is an attraction for visitors to buy livestock